Prevalence of plasmid-bearing and plasmid-free Chlamydia trachomatis infection among women who visited obstetrics and gynecology clinics in Malaysia - Yeow, T.C. (BioMed Central, 2016)
Background: The 7.5 kb cryptic plasmid of Chlamydia trachomatis has been shown to be a virulence factor in animal models, but its significance in humans still remains unknown. The aim of this study was to investigate the prevalence and potential involvement of the C. trachomatis cryptic plasmid in causing various clinical manifestations; including infertility, reproductive tract disintegrity, menstrual disorder, and polycystic ovarian syndrome (PCOS) among genital C. trachomatis-infected patients. Results: A total of 180 female patients of child bearing age (mean 30.9 years old, IQR:27-35) with gynecological complications and subfertility issues, who visited Obstetrics and Gynecology clinics in Kuala Lumpur, Malaysia were recruited for the study. Prevalence of genital chlamydial infection among these patients was alarmingly high at 51.1 % (92/180). Of the 92 chlamydia-infected patients, 93.5 % (86/92) were infected with plasmid-bearing (+) C. trachomatis while the remaining 6.5 % (6/92) were caused by the plasmid-free (-) variant. Our data showed that genital C. trachomatis infection was associated with infertility issues, inflammation in the reproductive tract (mucopurulent cervicitis or endometriosis), irregular menstrual cycles and polycystic ovarian syndrome (PCOS). However, no statistical significance was detected among patients with plasmid (+) versus plasmid (-) C. trachomatis infection. Interestingly, plasmid (+) C. trachomatis was detected in all patients with PCOS, and the plasmid copy numbers were significantly higher among PCOS patients, relative to non-PCOS patients. Conclusion: Our findings show a high incidence of C. trachomatis infection among women with infertility or gynecological problems in Malaysia. However, due to the low number of plasmid (-) C. trachomatis cases, a significant role of the plasmid in causing virulence in human requires further investigation of a larger cohort.